2015
DOI: 10.1097/ta.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of blunt traumatic aortic injury

Abstract: There have been changes in practice since the publication of the previous guidelines in 2000. Computed tomography of the chest with intravenous contrast is strongly recommended to diagnose clinically significant BTAI. Endovascular repair is strongly recommended for patients without contraindications. Delayed repair of BTAI is suggested, with the stipulation that effective blood pressure control must be used in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(67 citation statements)
references
References 50 publications
0
57
0
10
Order By: Relevance
“…2732 Specifically, current data suggest that delayed repair of low-grade (1 or 2) blunt thoracic aortic injuries (BTAI) is safe, and endovascular therapy is recommended as first-line treatment by 2015 EAST guidelines. 27 Delayed repair of BTAI is justified in the polytrauma patient where more immediate life-saving interventions (e.g. emergent laparotomy or craniotomy) are prioritized, and the aortic injury is temporized by medical blood pressure control prior to definitive repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2732 Specifically, current data suggest that delayed repair of low-grade (1 or 2) blunt thoracic aortic injuries (BTAI) is safe, and endovascular therapy is recommended as first-line treatment by 2015 EAST guidelines. 27 Delayed repair of BTAI is justified in the polytrauma patient where more immediate life-saving interventions (e.g. emergent laparotomy or craniotomy) are prioritized, and the aortic injury is temporized by medical blood pressure control prior to definitive repair.…”
Section: Discussionmentioning
confidence: 99%
“…emergent laparotomy or craniotomy) are prioritized, and the aortic injury is temporized by medical blood pressure control prior to definitive repair. 27 However, patients with high-grade (3 or 4) blunt aortic injuries should not be considered for delayed repair. 28 Current EAST and WTA guidelines recommend endovascular intervention for blunt hepatic 29,30 and splenic 31,32 injury only in hemodynamically stable patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Eastern Association for the Surgery of Trauma recommends that grade 3 injuries, defined as BTAI with pseudoaneurysm, undergo urgent endovascular repair,7 while the Society for Vascular Surgery (SVS) recommends early endovascular repair with medical therapy as a bridge to surgical intervention 8. However, in the setting of polytrauma in which a patient may present with major extrathoracic injuries, pharmacological management of blood pressure may obviate this option.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have shown a decrease in mortality in BTAI stable patients with delayed repair [14]. The Eastern Association for Surgery of Trauma recommends delayed repair with effective blood pressure control in this subset of patients [4].…”
Section: Medica Therapymentioning
confidence: 99%
“…In the past, the standard of care of traumatic vascular injuries was open surgical repair, and the in-hospital mortality for BTAI in the first 24 hours was up to 50% of patients [3,4]. However, in the last two decades, endovascular management for blunt trauma vascular injuries has significantly increased from 0.4% in 2002 to 13.2% in 2010.…”
Section: Introductionmentioning
confidence: 99%